Utilization Method Simple Additive Weighting in Decision Support Systems to Determine Outstanding Students - Nurulita, Khiara; Prakisya, Nurcahya PradanaTaufik; Maryono, Dwi (Digital Innovation, 2024)
Giving awards to outstanding students is one of the motivators so that students develop, improve, and maintain their achievements in the academic/non-academic field so that healthy competition arises between students in positive terms. However, in determining student achievement the determining factor is only based on the results of the national exam scores. The drawback is that it is considered subjective because students who have achievements do not necessarily get good test scores so a system is designed that can assist in determining outstanding students, namely the Decision Support System (SPK). This study uses the Systems Development Life Cycle prototyping model and research and development type of research. Data collection uses interviews, literature studies, and questionnaires. Testing the system with blackbox testing, assessing the media expert system and evaluating the system using the System Usability Scale (SUS) method. The research results show that the system is very feasible in the use and development of determining student achievement with effective and objective results. This is motivated by the acquisition of an average media expert score of 88% and a system evaluation by a user of 83.75. Because the value is in the range of 81-100, the system can be categorized as very feasible to use and develop.